An Expert System for Predicting Air Pollution Due to Development - Ahmed Kabbashi, Nassereldeen (1998)
Air is one of the important media for living creatures to survive their lives. The number of pollution complaints received by the Department of Environment (DOE) rose sharply and the number of air pollution complaints far exceeded other complaints, a few air pollutants called criteria air pollutants, can injure health, harm the environment, and cause property damage. In an environmental impact assessment (EIA) reports, the study to identify, predict and evaluate the impacts on the environment of a proposed project and to detail out the mitigating measures prior to project approval and implementation is very important. Due to shortage of manpower it is very difficult to verify that the developer or the project manager actually complies with the approved EIA guidelines. The purpose of this study is to develop a comprehensive expert system (ES) in air pollution that could be used as a tool in preparing an EIA evaluation and also as a tool to be used as an aid for approval and monitoring of an EIA study during the construction and operational stage of prescribed activities. This was carried out by: (1) detailed study of air impact analysis presented in EIA reports submitted to the DOE, (2) literature review about air quality and (3) Designing rules for air impact analysis to be incorporated into the EIA. Therefore, the application of a computer technology in the form of an expert system for air pollution using CLIPS helps in the analysis and management of EIA information.